STUDI LITERATUR TERKAIT PENGARUH PENGGUNAAN GADGET TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Kharisma Nurrohimah; Tunjungsari Sekaringtyas; Endang Wahyudiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is a literature study that aims to examine the effect of gadget use on elementary school students' learning motivation. Gadgets, as part of technological advancement, have the potential to increase learning motivation if used appropriately, such as as interactive media and information sources. However, excessive and unsupervised use can reduce learning motivation, disrupt concentration and lead to addiction. This review analyzes five relevant scientific articles that show that the effects of gadgets are significant and influenced by the intensity of use, the type of content, and the role of parental and teacher supervision. Therefore, wise and collaborative gadget management is needed to support students' learning process optimally.